2017
DOI: 10.1038/s41598-017-01512-x
|View full text |Cite|
|
Sign up to set email alerts
|

A reassortant H9N2 influenza virus containing 2009 pandemic H1N1 internal-protein genes acquired enhanced pig-to-pig transmission after serial passages in swine

Abstract: Avian H9N2 and 2009 pandemic H1N1 (pH1N1) influenza viruses can infect pigs and humans, raising the concern that H9N2:pH1N1 reassortant viruses could emerge. Such reassortants demonstrated increased replication and transmissibility in pig, but were still inefficient when compared to pH1N1. Here, we evaluated if a reassortant virus containing the hemagglutinin and neuraminidase of A/quail/Hong Kong/G1/1997 (H9N2) in the A/California/04/2009 (pH1N1) backbone could become better adapted to pigs by serial passagin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
10
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 15 publications
(11 citation statements)
references
References 42 publications
0
10
0
Order By: Relevance
“…One possible mechanism of this adaptation is that these H3N2 IAVs-S acquired internal genes derived from A(H1N1)pdm09 viruses. A previous study demonstrated that an avian H9N2 influenza virus adapted better to pigs when the internal genes were replaced by those from A(H1N1)pdm09 viruses (48). This possibility should be further explored concerning the H3N2 IAVs-S currently circulating in Japan.…”
Section: Discussionmentioning
confidence: 99%
“…One possible mechanism of this adaptation is that these H3N2 IAVs-S acquired internal genes derived from A(H1N1)pdm09 viruses. A previous study demonstrated that an avian H9N2 influenza virus adapted better to pigs when the internal genes were replaced by those from A(H1N1)pdm09 viruses (48). This possibility should be further explored concerning the H3N2 IAVs-S currently circulating in Japan.…”
Section: Discussionmentioning
confidence: 99%
“…Reassortment between two IAVs of different or the same origins have been well documented [79, 11, 1419, 38]. Previous studies tested the compatibility of emerging avian IAVs and endemic human influenza viruses, such as the compatibility of avian H9N2 with human H1N1 [39, 40], avian H5N1 with human H3N2 [8, 10, 41], and avian H5N1 with human H1N1 [42].…”
Section: Discussionmentioning
confidence: 99%
“…In addition to virus receptor binding attributes, compatibility between the co-circulating avian and swine or human IAVs will determine whether a new reassortant can be generated in swine. A number of studies have been performed to evaluate the compatibility of emerging avian IAVs and endemic human IAVs, such as avian H9N2 versus human H1N1 [7], avian H5N1 versus human H3N2 [810], and avian H5N1 versus human H1N1 [11]. The studies demonstrated that gene compatibility between viruses is subtype- and strain-dependent [7, 1012]; however, transmissible viruses are possibly derived from genetic reassortments between avian and human IAVs [13].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Viral RNA for sequencing was extracted from mouse lung, and in vitro culture supernatant samples using the High Pure Viral RNA Kit (Roche, Basel, Switzerland) according to the manufacturer’s protocol and eluted in UltraPure DNase/RNase-Free Distilled Water (ThermoFisher Scientific, MA, USA). Viral cDNA was synthesised using the Transcriptor First Strand cDNA Synthesis Kit (Roche) essentially as described previously ( Mancera Gracia et al, 2017 ). Briefly, two reactions were performed per sample, using either 2.5 µM CommonUni12A primer ( GCCGGAGCTCTGCAGATATCAGCAAAAGCAGG ) or 2.5 µM CommonUni12G primer ( GCCGGAGCTCTGCAGATATCAGCGAAAGCAGG ).…”
Section: Methodsmentioning
confidence: 99%